Chronic Kidney Disease: Underlying Molecular Mechanisms - Carvalho, Márcia; Belo, Luís (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Chronic kidney disease (CKD) is a worldwide public health problem that must be addressed. The global increase in CKD prevalence is associated with an increase in conventional disease risk factors (e.g., diabetes and hypertension), which may be exacerbated by additional variables such as environmental and occupational exposure to toxic compounds. Authors contributed to this Special Issue by highlighting the finding of potential novel biomarkers of the disease and more effective therapy alternatives, as well as works that enhance the understanding of CKD pathogenesis and its related complications.